The Role of Loneliness with Locus of Control in Early Adulthood - Rifani Alya Araminta; Aisya Putri Handayani; Hanna Christina Uranus (Edunity Kajian Ilmu Sosial dan Pendidikan, 2024)
Loneliness is an increasing problem among early adult individuals, especially at the age of 20-40 years. Locus of control, as individuals' beliefs about their ability to control outcomes in life, may play an important role in the experience of loneliness. This study aims to examine the effect of locus of control on the level of loneliness in early adult individuals. This study used a quantitative method with a survey approach, involving 250 early adult respondents selected by purposive sampling. Data were collected using an online questionnaire consisting of the UCLA Loneliness Scale and Levenson's Multidimensional Locus of Control Scale. The results of the analysis show that locus of control has a significant negative influence on the level of loneliness, with a coefficient of determination (R²) value of 0.283. This shows that 28.3% of variations in loneliness levels can be explained by locus of control. This study indicates that individuals with higher locus of control tend to experience lower levels of loneliness. The findings provide important insights in the development of interventions to support the mental health of early adult individuals and achieve the expected research objectives.